Adhesion of Human Mesenchymal Stem Cells and Differentiation of SH‐SY5Y Cells on Amyloid Fibrils. Issue 1 (November 2016) - Jacob, Reeba S.; Sen, Shamik; Maji, Samir K.
Summary: Amyloids are protein/peptide aggregates traditionally associated with many human disorders. However recent evidences suggest that amyloids are also capable of performing various native biological functions in host organisms. Many lower organisms including bacteria and algae use the highly ordered and adhesive property of amyloids for adhesion to host/substrates and/or for colonization, thus suggesting amyloids could serve as extracellular matrices (ECMs). Recently, we had reported that mammalian cells can adhere on amyloids using membrane‐fibril interactions and integrin‐based focal adhesion. In the current study, we demonstrate the nanotopography of amyloid fibrils for adhesion of human mesenchymal stem cells (hMSCs). Further, we also investigate the amyloid surface for differentiation of neuroblastoma cells SH‐SY5Y. Our present study delineates the role of amyloid self‐assembly in cell adhesion and differentiation.